2006
DOI: 10.1108/13563280610661697
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the influence of environmental labels on consumers

Abstract: Purpose-Despite research studies indicating strong support for labelling information, uncertainty remains with respect to how labels influence consumers. This paper attempts to empirically investigate how consumers who differ in terms of environmentalism respond to labels. Design/methodology/approach-The data were collected on an Australian sample using a structured questionnaire administered on the phone using quantum research (CATI) data collection services. A total of 155 questionnaires were completed and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
256
1
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(289 citation statements)
references
References 22 publications
18
256
1
14
Order By: Relevance
“…In the marketing literature knowledge of labels has received attention [5,[49][50][51]. Past research suggested that consumers prefer products that have a familiar seal on their packaging [52].…”
Section: Labelling Knowledgementioning
confidence: 99%
“…In the marketing literature knowledge of labels has received attention [5,[49][50][51]. Past research suggested that consumers prefer products that have a familiar seal on their packaging [52].…”
Section: Labelling Knowledgementioning
confidence: 99%
“…Ali and Amir [19] find that if a firm produces more green products, consumers have an intention to buy more from the firm. D'Souza et al [20] show that some consumers will buy green products even if the products are of lower quality than the alternative products. Meanwhile, these consumers would look for environmental information on labels.…”
Section: Introductionmentioning
confidence: 99%
“…When consumers are aware of the impact of their consumption on the environment, they would be more incline to behave in a more ecologically conscious manner. Consumers with vast knowledge regarding green issues tend to be motivated to buy green products and more inclined toward green consumption behavior (Barber et al, 2009;D'Souza et al, 2006). There is a possibility that a higher level of environmental knowledge would lead to a much better attitude toward the environment.…”
Section: Environmental Knowledgementioning
confidence: 99%